Effects of thermal stress on the optic and cerebral neurosecretory cells of brackiswater prawn, penaeus monodon (fabricius) - Ghosh, P.K; Nanda, D.k
Unsuitable temperatures untoward effects on the neurosecretory cells (NSCs) of the eye and brain in a penaeid prawn. P monodon. The cellsshowed multiple cytoarchitectural alteration suggesting overall impairment of secretion. The X-organ (optic) NSCs were more susceptible than the cerebral and exhibited marked engorgement and cessation of axonal transport in chill-coma (20.0degrees C). Marginal depletion with moderate axonal flow were obvious during high temperature (40 degrees C). Statistical data concerning cellular activity were consistent with histomorphic alterations in the photocephalic neurosecretory centers. Under such temperatures extremes, the sinus gland (SG) demonstrated minimal or insignificant quanta of neurosecretory material (NSM) very likely due to impaired axonal transport.